Freezing resistance in Patagonian woody shrubs: the role of cell wall elasticity and stem vessel size - Zhang, Yong Jiang (2016)
Freezing resistance through avoidance or tolerance of extracellular ice nucleation is important for plant survival in habitats with frequent subzero temperatures. However, the role of cell walls in leaf freezing resistance and the coordination between leaf and stem physiological processes under subzero temperatures are not well understood. We studied leaf and stem responses to freezing temperatures, leaf and stem supercooling, leaf bulk elastic modulus and stem xylem vessel size of six Patagonian shrub species from two sites (plateau and low elevation sites) with different elevation and minimum temperatures. Ice seeding was initiated in the stem and quickly spread to leaves, but two species from the plateau site had barriers against rapid spread of ice. Shrubs with xylem vessels smaller in diameter had greater stem supercooling capacity, i.e., ice nucleated at lower subzero temperatures. Only one species with the lowest ice nucleation temperature among all species studied exhibited freezing avoidance by substantial supercooling, while the rest were able to tolerate extracellular freezing from −11.3 to −20 °C. Leaves of species with more rigid cell walls (higher bulk elastic modulus) could survive freezing to lower subzero temperatures, suggesting that rigid cell walls potentially reduce the degree of physical injury to cell membranes during the extracellular freezing and/or thaw processes. In conclusion, our results reveal the temporal–spatial ice spreading pattern (from stem to leaves) in Patagonian shrubs, and indicate the role of xylem vessel size in determining supercooling capacity and the role of cell wall elasticity in determining leaf tolerance of extracellular ice formation.